Instrumentalismes contradictoires de la logique des idéologies dans une formation sociale inuit aborigène - Legros, Dominique (Anthropologica, 2022)
Nunamiut Inuit social formation is analysed in terms of two co-existing modes of production: (1) nomadic production and (2) collective corraling of huge migratory herds of caribou. In the absence of an ideology of descent from one common ancestor, cognatic kin reckoning is shown to prevent large group formation and to entail fragmentation of the population into isolated familial units of production. Whereas the fragmenting properties of the Nunamiut idea of kinship are in harmony with nomadic production, they hinder the functioning of the second and most productive mode of production. The analysis demonstrates how a classless social formation may be plagued by structural contradictions between ideology and production.